Factors for Predicting Favorable Outcome of Percutaneous Epidural Adhesiolysis for Lumbar Disc Herniation - Sang Ho Moon; Jae Il Lee; Hyun Seok Cho; Jin Woo Shin; Won Uk Koh (Pain Research and Management)
Background. Lower back pain is a common reason for disability and the most common cause is lumbar disc herniation. Percutaneous epidural adhesiolysis has been applied to relieve pain and increase the functional capacity of patients who present this condition. Objectives. In this study, we retrospectively evaluated the factors which predict the outcome of percutaneous epidural adhesiolysis in patients who were diagnosed with lumbar disc herniation. Methods. Electronic medical records of patients diagnosed with lumbar disc herniation who have received percutaneous epidural adhesiolysis treatment were reviewed. The primary outcome was the factors that were associated with substantial response of ≥4 points or ≥50% of pain relief in the numerical rating scale pain score 12 months after the treatment. Results. Multivariate logistic regression analysis demonstrated that the presence of high-intensity zone (HIZ) at magnetic resonance imaging was a predictor of substantial response to percutaneous epidural adhesiolysis for 12 months (P=0.007). The presence of a condition involving the vertebral foramen was a predictor for unsuccessful response after 12 months (P=0.02). Discussion and Conclusion. The presence of HIZ was a predictor of favorable long-term outcome after percutaneous epidural adhesiolysis for the treatment of lower back pain with radicular pain caused by lumbar disc herniation.